Physiological requirements in triathlon - Millet, G. P.; Vleck, V. E.; Bentley, D. J. (Journal of Human Sport & Exercise, 2011)
This article aims to present the current knowledge on physiological requirements in Olympic distance and Ironman triathlon. Showing the data available from a "traditional point of view" (aerobic power, anaerobic threshold, heart rate, running economy) and from a "contemporary" point of view (V?O2 kinetics), it emphasises where we are currently and the areas that remain unknown.